A ideia de religião e sentido ético na obra de Emmanuel Levinas - Campos, Fabiano Victor (Numen, 2023)
The objective of this paper is to delineate a panorama of the interaction between religion and ethics in the conception of philosopher Emmanuel Levinas, whose thought developed from the dialogue between two fundamental sources: Hebrew inspiration and Greek thought. Levinas is the bearer of a perspective that, without neglecting philosophical rigor and objectivity, leads us to an original ethical intelligibility, founded on the infinite right of the Other and the unlimited responsibility for others. In this context, the theme of religion is connected to the ethical sphere of intersubjective relations, established by the manifestation of the other man's face.